A systematic review of interventions to recognise, refer and diagnose patients with lung cancer symptoms - Mohamad M. Saab; Megan McCarthy; Michelle O’Driscoll; Laura J. Sahm; Patricia Leahy-Warren; Brendan Noonan; Serena FitzGerald; Maria O’Malley; Noreen Lyons; Heather E. Burns; Una Kennedy; Áine Lyng; et al. (npj Primary Care Respiratory Medicine, 2022)
Abstract Patients with lung cancer (LC) often experience delay between symptom onset and treatment. Primary healthcare professionals (HCPs) can help facilitate early diagnosis of LC through recognising early signs and symptoms and making appropriate referrals. This systematic review describes the effect of interventions aimed at helping HCPs recognise and refer individuals with symptoms suggestive of LC. Seven studies were synthesised narratively. Outcomes were categorised into: Diagnostic intervals; referral and diagnosis patterns; stage distribution at diagnosis; and time interval from diagnosis to treatment. Rapid access pathways and continuing medical education for general practitioners can help reduce LC diagnostic and treatment delay. Awareness campaigns and HCP education can help inform primary HCPs about referral pathways. However, campaigns did not significantly impact LC referral rates or reduce diagnostic intervals. Disease outcomes, such as LC stage at diagnosis, recurrence, and survival were seldom measured. Review findings highlight the need for longitudinal, powered, and controlled studies.